Managing for a change how to run community development projects - Davies, Anthony (London Intermediate Technology Publications, 1997)
Project management is a skill we have to learn and this book provides an insight into development project planning and management by guiding the reader through the stages from concept to completion. Topics covered include problem identification, mobilizing a group, solution identification and planning, resource identification and cost estimating, project funding, basic book-keeping and records, project supervision, project execution and post-project management. Each chapter has test exercises to reinforce the lessons. The language used is clear and simple, and there are illustrations and diagrams throughout.
Keywords: Community development -Management.